Effects of aerobic exercise intervention on serum cartilage oligomeric matrix protein levels and lymphocyte dna damage in obese elderly females - Cho, Su Youn (J Phys Ther Sci, 2016)
[Purpose] The aim of the reported research was to investigate the effects of regular aerobic exercise on cartilage oligomeric matrix protein and oxidative DNA damage in obese, elderly females. [Subjects and Methods] Sixteen class I obese, elderly females, according to World Health Organization criteria, were randomly and equally assigned to a control group (n=8) or an exercise group (n=8). The exercise group participated in exercise sessions of 60 minutes per day, 3 days per week, for a period of 8 weeks. [Results] After aerobic exercise intervention, weight, body mass index, body fat, waist circumference, and DNA damage (Tail moment) were significantly decreased, compared with baseline values. In contrast, serum cartilage oligomeric matrix protein levels were not significantly different among any groups or time-points. [Conclusion] Regular aerobic exercise may be effective for reducing obesity-induced high DNA damage levels in obese females, without causing the deformation or degradation of lower extremity articular cartilage.